2018
DOI: 10.3390/rs10020279
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Landslides—A Review

Abstract: Triggered by earthquakes, rainfall, or anthropogenic activities, landslides represent widespread and problematic geohazards worldwide. In recent years, multiple remote sensing techniques, including synthetic aperture radar, optical, and light detection and ranging measurements from spaceborne, airborne, and ground-based platforms, have been widely applied for the analysis of landslide processes. Current techniques include landslide detection, inventory mapping, surface deformation monitoring, trigger factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(107 citation statements)
references
References 19 publications
0
75
0
2
Order By: Relevance
“…Remote sensing (RS)-as an effective and rapid tool for monitoring large areas-is essential for the acquisition of geospatial data, which in turn constitutes the basis for risk assessment and management. RS is widely used for various aspects of the DRM, ranging from vulnerability [8] to rapid damage assessments [9], for diverse areas ranging from coastal ecosystems [10] to complex urban settings [11], and for disasters as diverse as landslides [12,13] or cyclones [14].Numerous methods have been developed to extract information from RS data to identify, characterize, or quantify different phases of the disaster risk cycle: response, recovery, prevention/mitigation, and preparedness [15]. However, early studies predominantly considered the physical side of the assessments for both pre-and post-disaster phases and hazard assessment, using direct observations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing (RS)-as an effective and rapid tool for monitoring large areas-is essential for the acquisition of geospatial data, which in turn constitutes the basis for risk assessment and management. RS is widely used for various aspects of the DRM, ranging from vulnerability [8] to rapid damage assessments [9], for diverse areas ranging from coastal ecosystems [10] to complex urban settings [11], and for disasters as diverse as landslides [12,13] or cyclones [14].Numerous methods have been developed to extract information from RS data to identify, characterize, or quantify different phases of the disaster risk cycle: response, recovery, prevention/mitigation, and preparedness [15]. However, early studies predominantly considered the physical side of the assessments for both pre-and post-disaster phases and hazard assessment, using direct observations.…”
mentioning
confidence: 99%
“…Remote sensing (RS)-as an effective and rapid tool for monitoring large areas-is essential for the acquisition of geospatial data, which in turn constitutes the basis for risk assessment and management. RS is widely used for various aspects of the DRM, ranging from vulnerability [8] to rapid damage assessments [9], for diverse areas ranging from coastal ecosystems [10] to complex urban settings [11], and for disasters as diverse as landslides [12,13] or cyclones [14].…”
mentioning
confidence: 99%
“…Previous work has shown that multi-source remote sensing methods can detect fast-moving landslide [18,19], capture clear morphological evidence [87] and insight the kinematics and their Figure 9. Deformation decomposed into seasonal (e.g., freeze thaw period) and secular trend (e.g., climate change) in permafrost regions.…”
Section: Resultsmentioning
confidence: 99%
“…Even a minimal change, such as a small-scale landslides in the land surface can influence the surface environment through various processes such as radiation and water and heat exchange [16]. Therefore, it is vital to monitor the shortand long-term effects of landslides [17].Multiple techniques have been employed in small-scale landslides investigations and analysis [18,19], such as (1) generating landslide inventories using Airborne Lidar Data [20], (2) evaluating susceptibility mapping with digital elevation models (DEMs) [21], (3) analyzing the temporal evolution with aerial photogrammetry [22], and (4) surveying the critical threshold for reactivating the landslide with geophysics [23]. In recent years, the high-resolution Synthetic Aperture Radar interferometry technique (InSAR) has proven to be an excellent tool to monitor the landslide on both the site-specific and the regional scale, including landslide hazard investigation, landslide monitor and landslide prediction [24][25][26][27].…”
mentioning
confidence: 99%
“…It can rapidly acquire high-precision terrestrial 3D models and can be applied to landslide identification, dynamic landslide deformation monitoring and acquisition of geomorphological features [31,32]. The LiDAR system is composed of a 3D laser scanning system, a control system and a power supply system [33][34][35][36]. The complete 3D laser scanning system includes a laser ranging and angle measuring system, a laser scanning system, an integrated charge-coupled device camera, and an internal control and correction system.…”
Section: Boundary Identificationmentioning
confidence: 99%